Locally recurrent chondrosarcoma of the pelvis and limbs can only be controlled by wide local excision. (March 2019) - Laitinen, M. K.; Parry, M. C.; Le Nail, L-R.; Wigley, C. H.; Stevenson, J. D.; Jeys, L. M.
Abstract : Aims: The purpose of this study was to investigate the potential for achieving local and systemic control after local recurrence of a chondrosarcoma of bone Patients and Methods: A total of 126 patients with local recurrence (LR) of chondrosarcoma (CS) of the pelvis or a limb bone were identified from a prospectively maintained database, between 1990 and 2015 at the Royal Orthopaedic Hospital, Birmingham, United Kingdom. There were 44 female patients (35%) and 82 male patients (65%) with a mean age at the time of LR of 56 years (13 to 96). The 126 patients represented 24.3% of the total number of patients with a primary CS (519) who had been treated during this period. Clinical data collected at the time of primary tumour and LR included the site (appendicular, extremity, or pelvis); primary and LR tumour size (in centimetres); type of operation at the time of primary or LR (limb-salvage or amputation); surgical margin achieved at resection of the primary tumour and the LR; grade of the primary tumour and the LR; gender; age; and oncological outcomes, including local recurrence-free survival and disease-specific survival. A minimum two years' follow-up and complete histopathology records were available for all patients included in the study. Results: For patients without metastases prior to or at the time of local recurrence, the disease-specific survival after local recurrence was 62.5% and 45.5% at one and five years, respectively. After univariable analysis, significant factors predicting disease-specific survival were grade (p < 0.001) and surgical margin (p = 0.044). After multivariable analysis, grade, increasing age at the time of diagnosis of local recurrence, and a greater time interval from primary surgery to local recurrence were significant factors for disease-specific survival. A secondary local recurrence was seen in 26% of patients. Wide margins were a good predictor of local recurrence-free survival for subsequent recurrences after univariable analysis when compared with intralesional margins (p = 0.002) but marginal margins did not reach statistical significance when compared with intralesional margins (p = 0.084) Conclusion: In cases of local recurrence of a chondrosarcoma of bone, we have shown that if the tumour is non-metastatic at re-staging, an increase in disease-specific survival and in local recurrence-free survival is achievable, but only by resection of the local recurrence with a wide margin. Cite this article: Bone Joint J 2019;101-B:266–271.